EFEKTIVITAS ASSERTIVE TRAINING UNTUK MENINGKATKAN PERILAKU ASERTIF SISWA DI SMP NEGERI 22 KOTA JAMBI - Putri, Putri; Yusra, Affan; Rahman, K.A. (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
The aim of this research is to increase the assertive behavior of students at SMP Negeri 22 Jambi City through the application of Assertive Training techniques. The method used is a quantitative approach with a pre-experimental design, one group pretest posttest design. The research sample consisted of 16 class VII students with low levels of assertive behavior, who were selected using the Purposive Sampling method. Data was collected through an assertive behavior scale consisting of 17 statement items. Hypothesis analysis was carried out using the non-parametric statistical Wilcoxon test to compare the pretest and posttest results. The results of the Wilcoxon test with the help of the SPSS ver 23 application, showed that there was a difference between the pretest and posttest, where at the pretest the students' assertive behavior was in the low category, then after being given treatment (posttest) it increased to the high category.